2022
DOI: 10.1186/s12912-022-01001-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the effect of diabetes education on self-care behaviors and glycemic control in the Turkey Nursing Diabetes Education Evaluating Project (TURNUDEP): a multi-center study

Abstract: Background Diabetes education in Turkey is provided by diabetes nurse educators in almost all healthcare organizations. However, the education is not standardized in terms of learning content, duration, and methods. This multi-center study was performed to assess the self-care behaviors and glycemic control following education provided to the patients with type 2 diabetes mellitus by diabetes nurse educators. Methods This was a descriptive and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(57 reference statements)
0
11
0
1
Order By: Relevance
“…Patients who got diabetes education three times or more, as well as patients who received education both individually and, in a group, had better levels of self-care and glycaemic control (p<0.05). 8 Results of another randomized trial concluded that the mean body mass index, waist circumference, and blood glucose levels are all reduced as a result of professional health educators providing structured diabetes self-care education to diabetics in primary health care. In a similar manner, it also lowers high blood pressure.…”
Section: Evidence From Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Patients who got diabetes education three times or more, as well as patients who received education both individually and, in a group, had better levels of self-care and glycaemic control (p<0.05). 8 Results of another randomized trial concluded that the mean body mass index, waist circumference, and blood glucose levels are all reduced as a result of professional health educators providing structured diabetes self-care education to diabetics in primary health care. In a similar manner, it also lowers high blood pressure.…”
Section: Evidence From Literaturementioning
confidence: 99%
“…Diabetes education is crucial for enhancing self-care among diabetic population. 8 Diabetes self-care has been described as an evolutionary process of knowledge or awareness development by learning to cope with the complexity of the disease in a social context. There is a critical need for reliable and effective metrics for diabetic self-management because patients and/or family handle the vast bulk of day-to-day care in diabetes.…”
mentioning
confidence: 99%
“…As a result of these discussions, the ICP is formulated in conjunction with the patient and his or her loved ones, as well as the patient's primary care physician and other nurses and senior caregivers 17,46 . This report is attached to the patient's medical records and contains all of the findings and conclusions from the first evaluation, as well as directions for nurses and caregivers written in clear language and providing suitable monitoring schedules (dates for future consultations and tests).…”
Section: Feet and Peripheral Neuropathymentioning
confidence: 99%
“…Kontrol grubunda ise gruplara göre izlemler arasında anlamlı fark vardı [43]. Altı haftalık ayak bakımı eğitimi [44] ve altı ay [45] sonrasında diyabetli bireylerin ayak bakımı bilgilerinde önemli bir artış bildirilen çalışmaların aksine başka bir çalışmada uygulama sonrası 6 ayda ayak öz bakım bilgisinin artmadığı bildirilmiştir. Araştırmacılar bu farklılığın örneklem sayısının azlığından kaynaklandığını vurgulamışlardır [46].…”
Section: Verilerin Değerlendirilmesiunclassified